1986
DOI: 10.1038/321439a0
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of herpesvirus ribonucleotide reductase by synthetic peptides

Abstract: Ribonucleotide reductase is an essential enzyme for DNA synthesis in all prokaryotic and eukaryotic cells; it catalyses the reductive conversion of ribonucleotides to deoxyribonucleotides. Several herpesviruses including herpes simplex virus type 1 (HSV-1), HSV-2, pseudorabies virus (PRV), equine herpesvirus type 1 (EHV-1) and Epstein-Barr virus (EBV) have been found to induce novel ribonucleotide reductase activities. There is evidence that the HSV-1 ribonucleotide reductase activity is virus-encoded and esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
133
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(139 citation statements)
references
References 15 publications
6
133
0
Order By: Relevance
“…Because protein-protein interactions play a key role in various mechanisms of cellular growth and differentiation, and viral replication, inhibition of these interactions is a promising novel approach for rational drug design against a wide number of cellular and viral targets (17,18). Synthetic peptides that disrupt protein-protein interactions have been successfully shown to act as inhibitors of HIV-1 protease (19), HIV-1 reverse transcriptase (20), herpes simplex virus ribonucleotide reductase (21), and thymidilate synthase (22). Binding of polypeptide hormones, growth factors, or cytokines to cell surface receptors activates dimerization (oligomerization) of the receptors, which leads to the signal transduction to the interior of the cell (23).…”
mentioning
confidence: 99%
“…Because protein-protein interactions play a key role in various mechanisms of cellular growth and differentiation, and viral replication, inhibition of these interactions is a promising novel approach for rational drug design against a wide number of cellular and viral targets (17,18). Synthetic peptides that disrupt protein-protein interactions have been successfully shown to act as inhibitors of HIV-1 protease (19), HIV-1 reverse transcriptase (20), herpes simplex virus ribonucleotide reductase (21), and thymidilate synthase (22). Binding of polypeptide hormones, growth factors, or cytokines to cell surface receptors activates dimerization (oligomerization) of the receptors, which leads to the signal transduction to the interior of the cell (23).…”
mentioning
confidence: 99%
“…Inhibition of this dimerization step would prevent the activation of the viral PR and, in turn, prevent the polyprotein processing, which is essential for viral maturation and infectivity (Kohl et al, 1988). The ability of oligopeptides to interfere with formation of a protein complex has been previously documented in vitro for two herpes simplex virus systems, the enzyme ribonucleotide reductase (Dutia et al, 1986;McClements et al, 1988), and the regulatory protein VP16 (Haigh et al, 1990). Our previous use of defective monomers or nonidentical subunits to exchange with wild-type PR homodimers 1245 in vitro produced catalytically defective heterodimers (Babe et al, 1991).…”
mentioning
confidence: 99%
“…This part of R2 has an important role in the association with the R1 protein [2][3][4][5][6][7][8][9]. The NMR observable segment also contains the conserved residues, Tyr-356 and Glu-350, that are invariable between species [22].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the carboxyl terminal part of protein R2 is important for the binding of protein R2 to protein R1 both in the E. eoli enzyme [24] and in the mammalian and Herpes simplex type I enzymes [5][6][7][8][9]. Truncations of C-terminal residues of protein R2 impair binding of protein R1 [2], and point mutations of conserved residues in the C-terminus reduces or abolishes catalytic activity [34].…”
Section: Introductionmentioning
confidence: 99%